Transcranial direct current stimulation modulates working memory and prefrontal-insula connectivity after mild-moderate traumatic brain injury - Quinn, Davin K.; Story-Remer, Jacqueline; Brandt, Emma; Fratzke, Violet; Rieger, Rebecca; Wilson, John Kevin; Gill, Darbi; Mertens, Nickolas; Hunter, Michael; Upston, Joel; Jones, Thomas R.; Richardson, Jessica D.; et al. (Frontiers in Human Neuroscience, 2022)
Background: Persistent posttraumatic symptoms (PPS) may manifest after a mild-moderate traumatic brain injury (mmTBI) even when standard brain imaging appears normal. Transcranial direct current stimulation (tDCS) represents a promising treatment that may ameliorate pathophysiological processes contributing to PPS. Objective/Hypothesis: We hypothesized that in a mmTBI population, active tDCS combined with training would result in greater improvement in executive functions and post-TBI cognitive symptoms and increased resting state connectivity of the stimulated region, i.e., left dorsolateral prefrontal cortex (DLPFC) compared to control tDCS. Methods: Thirty-four subjects with mmTBI underwent baseline assessments of demographics, symptoms, and cognitive function as well as resting state functional magnetic resonance imaging (rsfMRI) in a subset of patients (n = 24). Primary outcome measures included NIH EXAMINER composite scores, and the Neurobehavioral Symptom Inventory (NSI). All participants received 10 daily sessions of 30 minutes of executive function training coupled with active or control tDCS (2mA, anode F3, cathode right deltoid). Imaging and assessments were re-obtained after final training session, and assessments were repeated at one month. Mixed-models linear regression and repeated measures analyses of variance were calculated for main effects and interactions. Results: Both active and control groups demonstrated improvements in executive function (EXAMINER composite: p < 0.001) and posttraumatic symptoms (NSI cognitive: p=0.01) from baseline to one month. Active anodal tDCS was associated with greater improvements in working memory reaction time compared to control (p=0.007). Reaction time improvement correlated significantly with degree of connectivity change between the right DLPFC and the left anterior insula (p = .02). Conclusion: Anodal tDCS improved reaction time on an online working memory task in a mmTBI population, and decreased connectivity between executive network and salience network nodes. These findings generate important hypotheses for the mechanism of recovery from PPS after mild-moderate TBI.